College Students' Awareness of Irrational Judgments on Gambling Tasks: A Dual-Process Account. - Amsel, Eric; Close, Jason; Sadler, Eric; Klaczynski, Paul A. (Journal of Psychology, 2009)
In 2 studies, the authors examined college students' awareness of irrational judgments on gambling tasks. Participants could express a preference between 2 gambles with equivalent ratios (1:10 vs. 10:100) for Study 1 or no preference for Study 2. Participants also rated their certainty that each response option (i.e., 1:10, 10:100, no preference) was rational (analytically based processing) or irrational (experientially based processing of the ratio information). Only a minority of participants in each study was certain that the only analytically based, rational response was no preference. Those participants who were unaware of the analytically based rational response engaged in more formal and informal gambling activities in comparison with others. The authors interpreted the results as evidence of the importance of regulating dual analytical and experiential processes on gambling-related decision making and behavior. Reprinted by permission of the publisher.